Analisis Hubungan Asupan Zat Gizi Makro, Serat dan Sedentrary Lifestyle Dengan Obesitas Sentral Wanita Usia > 30 tahun di Kota Serang Banten - Faridi, Ahmad; Birwin, Alib; Ningtyas, Luthfiana Nurkusuma (Jurnal Kesehatan Indonesia, 2024)
Central obesity is more common in women aged ? 30 years. Upon entering the age of 30 years, the body’s metabolism decreases resulting in biological changes. If a person doesn’t control excessive food intake, body fat will begin to accumulate, and lack of physical activity can cause central obesity. This study aims to determine the relationship of energy intake, macro nutrients, fiber and sedentary lifestyle with central obesity. This cross sectional study has a sample of 106 women aged 30 years. Samples were selected using simple random sampling. Data related to respondent characteristics, energy intake, macro nutrients, fiber and sedentary lifestyle were collected using structured interviews. Central obesity data is obtained through measurement of waist circumference. Data analysis was performed using the chi-square test. 77.4% of respondents experience central obesity. The results showed that central obesity was significantly related to energy (p = 0.002), fat (p = 0.000), carbohydrate (p = 0.000), and sedentary lifestyle (p = 0.001). In contrast, protein intake (p = 0.082) and fiber (p = 0.226) did not show a significant relationship with central obesity. Conclusions Energy, fett, carbohydrate and sedentary lifestyle intake are associated with central obesity in women aged ? 30 years in the Serang village, Banten. It is recommended for women aged ? 30 years to pay attention to food intake and increase physical activity.